ISO 9000 2000 in focus - Nicholas; Smith (Australia : Nicholas and Smith Pty Limited [production company] ; Kuala Lumpur : On Target Training [distributor], 2000)
An organisation's quality management system plays an intergral part in its performance. this video will help equip managers to contribute to their organisatio's on-going improvement activities and business performance objectives
Keywords: Quality assurance -- Standards; ISO 9000 Series Standards; Quality control -- Standards